Recovery phase nutrition and insulin strategies for a female collegiate distance runner with type 1 diabetes mellitus: a case study - Schroeder, Amie (Kansas State University, 2022)
Background: There is scant published research regarding nutrition and insulin strategies for athletic performance in collegiate distance runners with Type 1 Diabetes Mellitus (CDRT1). Acute carbohydrate supplementation (CHOsup) and insulin reduction used to minimize hypoglycemia during exercise may result in deteriorated glycemic control post-exercise in CDRT1. The present case study of a CDRT1 investigated the effectiveness of a moderate-carbohydrate (ModCHO) diet and 24 hr insulin adjustment during the recovery phase for improved glycemic control and reduced use of acute strategies. Methods: During an 8-day period, a female CDRT1 followed a ModCHO (~4 g/kg/day) nutrition program. Recovery phase adjustments to insulin doses were made using an equation developed to estimate reduced insulin needs post-exercise, as a function of exercise intensity and duration. Daily training was performed in the fasted-state at 6:00 a.m. and included additional exercise strategies to reduce glycemic variability when needed. Daily blood glucose time in range (TIR) and use of CHOsup were assessed. Additionally, athlete well-being was determined using the Student-Athlete Well-Being Score survey at baseline, and days 1, 3, and 7. Results: Throughout the 8-day case study, the athlete’s mean TIR increased (77% versus < 50%) and the magnitude of glycemic excursions decreased (~3.8–15 versus ~3.0–26 mmol/L) relative to a prior comparison period. Minimal pre-exercise CHOsup was employed and CHOsup during exercise was not required. The athlete achieved a new lifetime best in the 5,000 m run and maintained positive well-being during the 8-day period. Conclusion: The present case study provides examples of recovery phase strategies (i.e., ModCHO diet and 24-hour insulin adjustments) that may support glycemic control and athletic performance in CDRT1 and provides potential starting points for nutrition and insulin strategies for use by athletes and coaches.
Keywords: Type 1 diabetes mellitus; Nutrition; Insulin; Distance runner; Strategies; Recovery phase